Co‐Designing a Primary Healthcare Intervention to Improve Diabetes Care in Mendoza, Argentina: A Qualitative Case Study. - Roberti, Javier; Mazzoni, Agustina; Guglielmino, Marina; Silva, Cecilia; Mazzaresi, Yanina; Falaschi, Andrea; Hirschhorn, Lisa R.; Parker, John J.; García‐Elorrio, Ezequiel (Health Expectations, 2026)
Background: In low‐ and middle‐income countries, primary healthcare (PHC) faces significant challenges in delivering effective care for chronic conditions, exacerbated by fragmented systems, resource limitations, and inequitable access. In Argentina, despite national strategies for non‐communicable diseases, implementation varies due to decentralised governance, leading to gaps in care. Here, we describe the codesign process of a contextually relevant intervention to strengthen diabetes care in Mendoza's PHC system. Methods: Using a qualitative case study approach, we conducted co‐design workshops (11/2024 – 02/2025) involving patients, healthcare providers, and policymakers. Activities included user journey mapping, world café, and prioritisation exercises guided by the Implementation Research Logic Model and Normalisation Process Theory. We collected data from activities and were analysed using reflexive thematic analysis. Results: Participants (n = 38) identified systemic barriers, including insufficient resources, poor coordination, and patient access challenges. Emotional engagement and creative exercises, such as role‐playing, fostered collaboration and innovative problem‐solving. The codesigned package emphasised multidimensional strategies, stakeholder collaboration, and systemic improvements tailored to local needs. Some of the proposed strategies included community asset mapping and social prescribing, protected appointment slots, digitalising patient records. Conclusion: This study shows that a structured codesign process, informed by theory and previous research, can support the development of a context‐specific intervention to improve diabetes care in PHC. The workshops enabled the identification of feasible implementation strategies that reflected diverse stakeholder perspectives. While the effectiveness of the intervention will be tested in future phases, the co‐design approach was feasible and well‐received in this setting, offering insights for similar efforts in other contexts. Patient or Public Contribution: Patients, family caregivers, and primary healthcare users actively participated in the co‐design process, contributing to the identification of challenges in diabetes care and the development of context‐specific solutions. Their lived experiences informed the previous studies that were used for the codesign process, the design and prioritisation of strategies through structured activities. Participants also reviewed the proposed components and provided feedback that helped shape the final intervention package.